Diagnostic performance of shear wave elastography in the identification of malignant thyroid nodules: a meta-analysis - Lin, Peiliang; Chen, Minqi; Liu, Baoxian; Wang, Siwen; Li, Xiaoxi (European radiology, 2014)
Objective This meta-analysis aimed to assess the performance of shear wave elastography (SWE) in the identification of malignant thyroid nodules. Methods Web of Science, Scopus, PubMed, and the references of narrative reviews were searched for relevant studies with a publication date through October 2013. The methodological quality was assessed using QUADAS tools. Data synthesis was calculated using the bivariate mixed-effects regression model. Results Of the 131 studies identified, 15 (11.5 %) were included, in which SWE, point-SWE or 2D SWE, was used to evaluate 1,867 thyroid nodules in 1,525 patients. Methodological assessment revealed study quality was moderate to high. The pooled sensitivity, specificity, and area under the summary receiver operating characteristic curve of SWE for detecting malignant thyroid nodules were 84.3 % (95 % confidence interval [CI], 76.9–89.7 %), 88.4 % (95 % CI, 84.0–91.7 %), and 93 % (95 % CI, 90–95 %), respectively. As a screening tool, positive and negative predictive values were 27.7–44.7 % and 98.1–99.1 %, respectively, calculated with a malignance prevalence of 5–10 % in thyroid nodules. A publication bias regression test revealed no significant small-study bias. Conclusions SWE is a highly accurate diagnostic modality for the identification of malignant thyroid nodules, with promise for integration into routine imaging protocols for thyroid nodules. Key Points • Shear wave elastography (SWE) is a group of novel ultrasound-based technologies . • Meta-analysis was employed to assess relevant studies of SWE of thyroid nodules . • SWE had high sensitivity and specificity in identifying malignant thyroid nodules . • The high negative predictive value of SWE can reduce unnecessary biopsies .